Reaction Time and Attention in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Reaction time, attention and impulsivity in 112 children with epilepsy (4.5-13 years) were studied using a computerized test at the Division of Neurology, Children's Hospital Los Angeles, Los Angeles, CA.